PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN GRAND JAYA RAYA RESORT & CONVENTION HOTEL CIPAYUNG BOGOR (Studi Korelasi Antara Kepuasan Kerja Dan Motivasi Kerja Dengan Kinerja Karyawan Grand Jaya Raya Resort & Convention Hotel Cipayung Bogor) - Giyanto Giyanto (Majalah Ilmiah Bijak, 2016)
The main factor we do have to figure out in judging someone’s work performance is satisfaction in work and work  motivation, Satisfaction means having an exciting feeling deep inside someone’s heart in order to raise the spirit of work. meanwhile a motivation is another important element  to  encourage someone in accomplishing a  better achievement. There is not  doubt at all that both satisfaction and motivation will definetily bring the entrie employee to a better work performance. It is a compulsory  for every employee to possess a high work motivation as well as its satisfactory in work. Both  high motivation and its satisfactory   in work will eventually carry out all the employees to a brighter work performance.The research formula as follows : (1) The influence of partial satisfaction in work towards the employee’s work performance, (2) The influence of partial work motivation towards the employee’s work performance, (3) The influence of simultaneous both satisfaction in work of work motivation  happening or done at the same moment towards the employees of Grand Jaya Raya Resort and Convention Hotel Cipayung Bogor. The use of analysis method is based on multiple linear regressive method as well as hypothetical linear examination. Operated by the usage of SPSS program ver.17.0. The writer’s research object goes to satisfaction in work , work motivation and its influence towards the work performance of the employees of Grand  Raya Resort and Convention Hotel Cipayung Bogor. The research population has taken into the entrie employee of Grand Raya Resort and Convention Hotel Cipayung Bogor with the total number of 137 employees. To  determine the research sample, the writer used stratified random sampling with the total determine of 58 respondents.  The SPSS  ver.17 .0 program obstained coefficient determination result  R-Square / R2 = 0,669 at the level α = 5%. where the examination towards determined coefficient done by  “test-F” resulted smaller probability than use of examination done in research  ( Sig. < α or 0,000 < 0,05 due to the equality model of multiple regressive Y = - 193.543 + 4.888X1 + 2.184X2. The abovementioned  result indicates that simultaneous satisfaction in work and work motivation will influence the work performance at the same moment, it has been  proven that the third hypotesis has mentioned abviously that satisfaction in work and work motivation at the same time will simultaneously be influencing the employee’s work performance. A better work satisfactory and its motivation shall somehow be done constantly, due to proven result of the research revealed that the constant number b0   = less than 1 even minus ( - 193.543 ). On the other hand, it also revealed that the variable of work satisfactory and work motivation ought to be done to maintain the employee’s work performance .